Arbitrability of disputes involving antitrust issues in Brazil and the protection of free competition - Coelho, Gustavo Flausino; da Silva, Ricardo Villela Mafra Alves (Revista Semestral de Direito Empresarial, 2023)
<div class="elementor-element elementor-element-262160f elementor-widget elementor-widget-jet-listing-dynamic-field" data-id="262160f" data-element_type="widget" data-widget_type="jet-listing-dynamic-field.default"> Law no. 9,307/1996 (Brazilian arbitration law) was enacted as part of the liberalization process of the Brazilian economy with the purpose of providing a more reliable mechanism of dispute resolution for parties of a contract. A few years before, Law no. 8,884/1994 was enacted to strengthen the protection of competition in Brazil. Currently, Law no. 12,529/2011 is the antitrust law in force in Brazil, which introduced deep changes in competition policy. Due to the fundamental principles of the economy established by the Brazilian Constitution, disputes in connection with antitrust issues usually involve both patrimonial rights and matters of public policy. In this sense, the scope of this study is to verify the possibility of using arbitration to resolve disputes involving antitrust matters using a law-and-economics approach, in view of the incentives of a party to adopt anticompetitive behavior. <div class="elementor-element elementor-element-d48b882 elementor-widget elementor-widget-jet-listing-dynamic-field" data-id="d48b882" data-element_type="widget" data-widget_type="jet-listing-dynamic-field.default">